2007
DOI: 10.1530/eje-07-0223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance versus endurance training on serum adiponectin and insulin resistance index

Abstract: Purpose: The purpose of the present study was to investigate the effects of resistance and endurance training on serum adiponectin and insulin resistance index (S I ) in healthy men. Methods: Twenty-four healthy males (age, 35-48 years) participated in the study. The subjects were randomly assigned to one of three groups: endurance training group (nZ8), resistance training group (nZ8) and control group (nZ8). Blood samples were taken in fasting state from all subjects. The experimental groups performed either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
3
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 44 publications
8
106
3
8
Order By: Relevance
“…Obese individuals with higher fitness levels generally have lower mortality rates compared to sedentary normalweight counterparts [33]. Previous studies have shown increases in VO 2max from baseline levels after resistance exercise training [34] and combined aerobic and resistance exercise training [7,8,33]. In our study, a moderateintensity of 60% of estimated HRR was used for aerobic exercise to target greater fat oxidation rather than cardiorespiratory fitness improvements per se [35].…”
Section: Discussionmentioning
confidence: 90%
“…Obese individuals with higher fitness levels generally have lower mortality rates compared to sedentary normalweight counterparts [33]. Previous studies have shown increases in VO 2max from baseline levels after resistance exercise training [34] and combined aerobic and resistance exercise training [7,8,33]. In our study, a moderateintensity of 60% of estimated HRR was used for aerobic exercise to target greater fat oxidation rather than cardiorespiratory fitness improvements per se [35].…”
Section: Discussionmentioning
confidence: 90%
“…Perhaps the subjects in the current study are the reason for the difference in the results of the present study. Ahmadizad et al examined the effect of aerobic exercise against resistance on adiponectin and concluded that there is a negative significant relationship between adiponectin levels and percentage of body fat compared to WHR and BMI [36]. Coker et al investigated the effect of exercise intensity (50% vs. 70% peak oxygen consumption) abdominal fat and adiponectin levels in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Il semble aussi que les exercices de résistance de faible intensité provoquent une augmentation du contenu en GLUT-4, des récepteurs insuliniques, de la glycogène synthétase et de la protéine kinase B sans augmentation de la masse musculaire [48]. Enfin, deux études ont montré qu'une combinaison d'exercices aérobies et de résistance pouvait améliorer la sensibilité à l'insuline chez l'enfant sans variation de la composition corporelle [21] ou du taux sérique d'adiponectine [47].…”
Section: Synthèse Revuesunclassified